Penerapan Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) ditinjau dari Multiple Intelligences - Septiana, Frika; Mujib, Mujib; Negara, Hasan Sastra (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this research is to know if there are: (1) the influence of PMRI approach to the problem-solving ability of mathematical learners; (2) the influence between multiple intelligences capability categories of mathematical problem solving abilities; (3) there is an interaction between PMRI approach with multiple intelligences on mathematical problem solving ability. This research is a quasi-experimental design research with 2 × 3 factorial design. Sampling technique in this research use probability sampling with cluster random sampling. The research instrument used is the test of mathematical problem-solving ability and multiple intelligences questionnaire. The resulting data of mathematical problem-solving test were analyzed by using another test of two different cell paths. The result of the research shows that: (1) there is an influence of PMRI approach to students' mathematical problem solving ability; (2) there is influence between categories of multiple intelligences ability in mathematical problem solving ability; (3) there is no interaction between PMRI approach with multiple intelligences on mathematical problem solving ability.